Levels of circulating angiogenic cells are not altered in women with endometriosis. - Webster, K; Kennedy, S; Becker, C (2013)
STUDY QUESTION: Are levels of circulating angiogenic cells (CACs) affected by the presence of endometriosis? SUMMARY ANSWER: Levels of CACs are equivalent in women with and without endometriosis. WHAT IS KNOWN ALREADY: Murine models have suggested a role for CACs in the development of endometriosis, but their levels in humans have not yet been studied. STUDY DESIGN, SIZE, DURATION: Eighty-seven women participated in this study. Recruitment took place from July 2010 to May 2012. PARTICIPANTS/MATERIALS, SETTING, METHODS: All women underwent laparoscopy for investigation of symptoms suggestive of endometriosis. Thirty women had no evidence of endometriosis, and 47 women were found to have endometriosis at laparoscopy. CAC levels were determined in peripheral blood by flow cytometry in 64 women. Colony forming unit (CFU) analysis was conducted in 30 women. A separate group of 10 healthy, asymptomatic women donated blood at four time points to assess the effect of the menstrual cycle on CAC levels. MAIN RESULTS AND THE ROLE OF CHANCE: For the whole sample, CAC levels (0.0797 ± 0.0052%) and CFU number (10.68 ± 1.98) were equivalent in women with and without endometriosis. CAC levels and CFU number were also unaffected by the stage of disease. No changes in CACs were detected during the menstrual cycle. LIMITATIONS, REASONS FOR CAUTION: A difference of at least one standard deviation between the groups would be required to detect a difference with this sample size. Therefore, while CAC levels are not a useful biomarker of disease it is still possible that they are modestly altered by the presence of endometriosis. We did not describe specific types of lesion and it is possible that CAC elevation only occurs when vessel development is at its most prolific. Furthermore, although signals from endometriotic lesions may recruit CACs from blood, this may be insufficient to alter peripheral levels. WIDER IMPLICATIONS OF THE FINDINGS: These data show that CACs are not a useful biomarker of endometriosis and indicate that they may be unaffected by the presence of this disease. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by grants from the MRC (New Investigator Award, G0601458 to C.M.B.), the Oxford Partnership Comprehensive Biomedical Research Centre with funding from the Department of Health's NIHR Biomedical Research Centres Scheme and the Oxfordshire Health Services Research Committee (OHSRC). There are no conflicts of interest to be declared.